Wave-absorbing heat-conducting flexible electromagnetic functional composite material and preparation method thereof

By using dendritic silver-clad copper powder, boron nitride nanosheets, carbonyl iron powder and the introduction of boron nitride fabrics in flexible electromagnetic materials, a multifunctional network structure is built, and the existing materials have been solved in high-frequency electromagnetic waves. The performance conflict problem in attenuation and thermal conductivity has achieved comprehensive performance of high-frequency wave absorption, high thermal conductivity and low density.

CN119495955AActive Publication Date: 2025-02-21AEROSPACE INST OF ADVANCED MATERIALS & PROCESSING TECH
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411501857.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-25
Publication Date
2025-02-21
Estimated Expiration
2044-10-25

AI Technical Summary

Technical Problem

There is a tendency for existing flexible electromagnetic materials to increase and decrease in performance in high-frequency electromagnetic wave attenuation and thermal conductivity, and it is difficult to meet the comprehensive performance requirements of high-frequency attenuation, high thermal conductivity and low density at the same time.

Method used

By combining dendritic silver-clad copper powder, boron nitride nanosheets, and carbonyl iron powder, and introducing boron nitride fabric into the matrix material to build a multifunctional network structure to prepare high-frequency wave absorption, high thermal conductivity, Low-density silicone rubber-based electromagnetic functional composite material.

Benefits of technology

The materials have been improved in high-frequency electromagnetic attenuation, thermal conductivity and lightweight, and can meet the application requirements of high-performance antenna systems for wave absorbing/thermal conducting materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005102814850000051
    Figure BDA0005102814850000051
  • Figure BDA0005102814850000061
    Figure BDA0005102814850000061
Patent Text Reader

Abstract

The invention discloses a wave-absorbing heat-conducting flexible electromagnetic functional composite material and a preparation method thereof, and belongs to the field of composite materials. Dendritic silver-coated copper powder, boron nitride nanosheets and carbonyl iron powder are compounded and mixed, a boron nitride fabric is introduced into a base material, a multifunctional network structure is systematically constructed through multiple dimensions, cross-scale and multiple components, and the silicone rubber-based electromagnetic functional composite material with high-frequency wave absorption, high heat conduction and low density is prepared. The wave-absorbing / heat-conducting material has the characteristics of high-frequency attenuation, high heat conductivity, low density and the like, and can meet the application requirements of a high-performance antenna system on the wave-absorbing / heat-conducting material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of composite materials, and in particular relates to a wave-absorbing, heat-conducting, flexible electromagnetic functional composite material and a preparation method thereof. Background Art

[0002] High-performance antenna systems are developing in the direction of high-power radiation, high-frequency transmission and reception, and strong stealth. The supporting electromagnetic functional materials of the antenna system have comprehensive performance requirements such as high-frequency loss clutter, control of surface current radiation, high temperature resistance, high thermal conductivity, and lightweight. However, with the high degree of integration of the overall space, the requirements for the integration of multifunctional materials are also getting higher and higher. Therefore, the research and development of an electromagnetic functional material with high-frequency attenuation function, high thermal conductivity, high temperature resistance, and low density has become one of the important links to solve the high-performance development of antenna systems. The present invention is to develop a high-thermal conductivity, lightweight and flexible electromagnetic functional composite material based on the dual mechanisms of conductivity loss and magnetic loss.

[0003] At present, multifunctional flexible electromagnetic materials are mainly obtained by adding various absorbers and traditional thermal conductive fillers to the rubber matrix to obtain materials with both thermal conductivity and wave absorption functions. One is to achieve the continuous integrity of the thermal conductive structure by increasing the network density of the filler in the matrix, thereby achieving efficient heat conduction; the other is to add absorbent fillers with different loss mechanisms to give the material a good electromagnetic wave absorption effect. However, there is a trend of performance loss between these two approaches, so it is necessary to carefully design and adjust the filler type, structure type, distribution ratio, interface characteristics, and molding process in the flexible material technology to achieve the technical goals of multifunctional and high-performance materials.

[0004] Dendritic silver-coated copper powder has high electrical conductivity, thermal conductivity and dimensional structural integrity, but its impedance matching is poor and it is difficult to achieve electromagnetic wave absorption under a wide frequency band; boron nitride, as an insulating thermal conductive material, not only has a high thermal conductivity, but also has excellent electrical insulation and a low dielectric constant. It is a good choice for adjusting the impedance matching characteristics of absorbing materials; carbonyl iron powder is one of the absorbers with better magnetic characteristics at present, which helps to adjust the absorption bandwidth and absorption intensity, but its density is high and its intrinsic thermal conductivity is poor. Adding too much is not conducive to reducing the weight of the overall absorbing material, and it cannot significantly improve the thermal conductivity. Summary of the invention

[0005] The purpose of the present invention is to compound and mix dendritic silver-coated copper powder, boron nitride nanosheets, and carbonyl iron powder, and introduce boron nitride fabric into the matrix material, so as to systematically construct a multifunctional network structure through multi-dimensional, cross-scale, and multi-component methods, and prepare a silicone rubber-based electromagnetic functional composite material with high-frequency wave absorption, high thermal conductivity, and low density.

[0006] The objective of the present invention is achieved through the following technical solutions:

[0007] A method for preparing a wave-absorbing, heat-conducting, flexible electromagnetic functional composite material, comprising the following steps:

[0008] (1) premixing dendritic silver-coated copper powder, P-type carbonyl iron powder, Q-type carbonyl iron powder, and boron nitride nanosheets to obtain a thermally conductive and microwave-absorbing composite powder;

[0009] (2) adding a coupling agent to the obtained thermal conductive and wave absorbing composite powder, mixing the mixture, and obtaining an activated thermal conductive and wave absorbing composite powder;

[0010] (3) adding the activated heat-conducting and wave-absorbing composite powder to methylphenyl silicone rubber for initial mixing to obtain a wave-absorbing and heat-conducting electromagnetic slurry;

[0011] (4) adding a certain amount of fumed silica and diisopropylbenzene di-tert-butyl peroxide to the obtained wave-absorbing and heat-conducting electromagnetic slurry, performing secondary mixing, and obtaining a flexible electromagnetic slurry after mixing evenly;

[0012] (5) repeatedly thin-passing the obtained flexible electromagnetic slurry material, and then pressing it into a thin sheet of rubber material;

[0013] (6) calendering the obtained flaky rubber material and the boron nitride fabric for preforming, and then stacking them into an unvulcanized prepreg;

[0014] (7) placing the obtained unvulcanized prepreg between two magnets for arrangement, then cutting it into strips and laying them flat, then flipping the strips 90° horizontally and laminating them side by side to obtain a layered unvulcanized strip;

[0015] (8) The obtained layered unvulcanized rubber material is subjected to hot pressing and vulcanization molding to obtain a wave-absorbing, heat-conducting, flexible and electromagnetic functional composite material.

[0016] Further, by mass, 127.5-178.5 parts of dendritic silver-coated copper powder, 12.75-25.5 parts of P-type flaky carbonyl iron powder, 12.75-51 parts of Q-type spherical carbonyl iron powder, 51-63.75 parts of boron nitride nanosheets, 1.275-5.1 parts of coupling agent, 40-45 parts of methylphenyl silicone rubber, 0.5-1.2 parts of fumed silica, and 0.4-0.45 parts of di-tert-butyl peroxide diisopropylbenzene are weighed.

[0017] Furthermore, in step (1), the length of the dendritic silver-coated copper powder filler is 11-18 μm, the particle size of the P-type flaky carbonyl iron powder D50 is 3.5-6.0 μm, the particle size of the Q-type spherical carbonyl iron powder D50 is 3-5 μm, and the particle size of the boron nitride nanosheet D50 is 0.05-0.2 μm.

[0018] Furthermore, the premixing condition in step (1) is mixing at a rotation speed of 12-25 rpm for 1-2 hours.

[0019] Furthermore, in step (2), the coupling agent is one of KH-550, KH-560, A-151, and GR-401.

[0020] Furthermore, in step (2), the mixing treatment is carried out at room temperature for 0.5-2h.

[0021] Furthermore, in step (3), the initial mixing is for 30-40 minutes, and the specific mixing conditions are 10-12 rpm for 12-15 minutes in the first stage, 15-20 rpm for 10-15 minutes in the second stage, and 8-10 rpm for 8-10 minutes in the third stage.

[0022] Furthermore, in step (4), the secondary mixing is performed for 10-15 minutes, and the order of adding materials is as follows: adding fumed silica in the first stage and adding diisopropylbenzene di-tert-butyl peroxide in the second stage. The specific mixing conditions are 20-25 rpm for 8-11 minutes in the first stage and 15-18 rpm for 2-4 minutes in the second stage.

[0023] Furthermore, in step (5), the thin pass treatment is repeated 10-16 times, and the thin pass treatment is divided into three stages, the first stage is thin pass 3-5 times with a roller distance of 1-1.2 mm, the second stage is thin pass 5-7 times with a roller distance of 0.6-0.8 mm, and the third stage is thin pass 2-4 times with a roller distance of 0.2-0.4 mm.

[0024] Furthermore, the thickness of the flaky rubber material in step (5) is 0.25-0.3 mm.

[0025] Furthermore, in step (6), the boron nitride fabric single filament has a diameter of 3-10 μm and a thickness of 0.1 mm.

[0026] Furthermore, in step (6), the calendering preforming condition is to calender the composite at 5-8 rpm, and then stack to form 7 layers, and the thickness of the uncured prepreg is 2-2.5 mm.

[0027] Furthermore, in step (7), two NdFeB magnets with a spacing of 8-15 cm are placed in the middle for magnetron treatment, the magnetic field strength is 1200-1850 Gs, and the magnetron treatment time is 4-6 hours; and then the rubber material is cut into 1-3 cm wide strips.

[0028] Furthermore, in step (8), the hot pressing vulcanization molding conditions are hot pressing at 145-170° C. and 10-15 MPa for 10-15 min, and post-treatment at 200° C. for 30 min.

[0029] A wave-absorbing, heat-conducting, flexible electromagnetic functional composite material is prepared by the above preparation method.

[0030] The present invention uses phenyl silicone rubber as a flexible matrix, dendritic silver-coated copper powder, carbonyl iron powder, and boron nitride nanofiller as multifunctional composite components, pre-mixes them through a V-type mixer, and uses a kneader to mix the composite powder with the silicone rubber matrix to prepare a high-viscosity flexible electromagnetic thermal conductive slurry; the boron nitride fabric and the electromagnetic thermal conductive slurry are calendered into sheets and cut and arranged through a calendering and coating method, and finally the layers are sequentially laid and heated and pressed under a flat vulcanizer to prepare a lightweight flexible electromagnetic functional material, which has the characteristics of high-frequency attenuation, high thermal conductivity, low density, etc., and can meet the application requirements of high-performance antenna systems for absorbing / thermal conductive materials.

[0031] The innovative features of the present invention are as follows:

[0032] Innovation 1: In the formula of the main absorber, four modified fillers with different functional types are used, namely, dendritic silver-coated copper powder, flaky carbonyl iron powder, spherical carbonyl iron powder, and boron nitride nanosheets. The different content ratios are changed to tune the electromagnetic wave attenuation performance of the flexible electromagnetic loss material in the high-frequency range. At the same time, the V-type powder premixing method is used to effectively reduce the agglomeration phenomenon between composite powders with different morphologies. The invention adopts the dendritic silver-coated copper powder. First, it has a branched micron-level morphology, which is conducive to the formation of a heat conduction path as a heat conduction trunk structure; second, it helps to enrich the electromagnetic loss mechanism of the material within a suitable addition range, which is conducive to high-matching electromagnetic absorption. The invention blends the content of flaky and spherical carbonyl iron powders to form an electromagnetic functional structure. The invention utilizes the thermal conductive trunk structure composed of dendritic silver-coated copper, the electromagnetic functional structure composed of carbonyl iron powder, and the functional interlayer bonding structure composed of boron nitride nanosheets and boron nitride fabrics. Through the functional integration of these structures, the high-frequency electromagnetic attenuation effect can be improved, and ultimately both attenuation and thermal conductivity are significantly improved.

[0033] Innovation 2: In the thermal conductive filler formula, nano-scale ultra-thin boron nitride nanosheets and submicron silver-coated copper powder are used to combine with each other. While ensuring that the electromagnetic parameters are not affected (the dielectric constant and magnetic permeability are stable and not disordered), they can be overlapped and isolated with the absorbing functional components to form a thermal conductive microstructure network;

[0034] Innovation point 3: In the construction of flexible electromagnetic material structure, boron nitride fiber fabrics and flexible electromagnetic slurry are stacked on each other and arranged through thin channels and magnetically controlled to construct a dual-functional structure of wave absorption / heat conduction network from the perspective of structure and preparation method.

[0035] The present invention has achieved the following beneficial effects:

[0036] (1) The present invention aims at the electromagnetic attenuation, impedance matching, and thermal conductivity and transmission characteristics unique to different types of fillers. By adjusting the ratio between conductive silver-coated copper, sheet / spherical carbonyl iron powder, and boron nitride nanosheets, a multi-scale and multi-morphological functional filler system is formed, which can realize the characteristics of high frequency strong attenuation and high thermal conductivity of flexible materials;

[0037] (2) The present invention addresses the problem of differences and randomness in the heat transfer performance of thermal conductive and absorbing materials in omnidirectional paths. Boron nitride fiber fabrics are added to the three-dimensional structure of the material, and the heat conductive path structure is further improved through mechanical orientation and magnetic control arrangement. The material also has the characteristics of stable dielectric properties, dual absorption loss mechanism, and low density, thereby achieving the characteristics of high thermal conductivity and strong attenuation of the material. DETAILED DESCRIPTION

[0038] The present invention is further described below in conjunction with specific examples, but the protection scope of the product prepared by the present invention and the method for preparing the product is not limited to the examples. The silicone rubber used in the examples is methyl phenyl silicone rubber, and its complex dielectric constant is 2.8-0.01j and its complex magnetic permeability is 1.1-0.01j.

[0039] Example 1

[0040] Weigh 127.5g of dendritic silver-coated copper powder, 25.5g of P-type flaky carbonyl iron powder, 51g of Q-type spherical carbonyl iron powder, and 63.75g of boron nitride nanosheets, mix them at a speed of 12rpm for 1h, then add 5.1g of coupling agent into the barrel, mix at room temperature for 0.5h, and obtain a wave absorbing and thermally conductive composite powder after activation treatment;

[0041] Weigh 40g of methylphenyl silicone rubber and composite powder, knead and mix at 10rpm for 12min in the first stage, 15rpm for 10min in the second stage, and 8rpm for 8min in the third stage, then add 0.5g of fumed silica and 0.40g of di-tert-butyl peroxide diisopropylbenzene, knead and mix at 20rpm for 8min in the first stage and 15rpm for 2min in the second stage; further, pass the rubber material through 3 times at a roller distance of 1.0mm in the first stage and 1.0mm in the second stage. 0.6mm thin pass 5 times, three-section roller spacing 0.2mm thin pass 2 times; then the sheet slurry and 0.1mm thick boron nitride fiber are calendered and compounded and stacked in 7 layers; then the sheet is placed between two 1200Gs magnetic field strength neodymium iron boron magnets with a spacing of 8cm and treated for 4 hours, further cut into 1cm wide strips of rubber, turn each strip over and then stick them together; finally, hot press at 145℃ and 10MPa for 15min, and then high temperature treatment in a 200℃ oven for 30min.

[0042] Example 2

[0043] Weigh 178.5g of dendritic silver-coated copper powder, 12.75g of P-type flaky carbonyl iron powder, 12.75g of Q-type spherical carbonyl iron powder, and 51g of boron nitride nanosheets, mix them at a speed of 25rpm for 2h, then add 1.275g of coupling agent into the barrel, mix at room temperature for 2.0h, and obtain a wave absorbing and thermally conductive composite powder after activation treatment;

[0044] Weigh 45g of methylphenyl silicone rubber and composite powder, knead and mix at 12rpm for 15min in the first stage, 20rpm for 15min in the second stage, and 10rpm for 10min in the third stage, then add 1.2g of fumed silica and 0.45g of di-tert-butyl peroxide diisopropylbenzene, knead and mix at 25rpm for 11min in the first stage and 18rpm for 4min in the second stage; further, pass the rubber material through 5 times on a roller with a distance of 1.2mm in the first stage, and roll it on the second stage for 10min. The sheet was rolled 7 times with a distance of 0.8mm and 4 times with a distance of 0.4mm between three rollers. The sheet was then calendered and compounded with 0.1mm thick boron nitride fiber and stacked in 7 layers. The sheet was then placed between two 1850Gs NdFeB magnets with a distance of 15cm and treated for 6 hours. The sheet was further cut into 3cm wide strips of rubber, and each strip was turned over and bonded to each other. Finally, it was hot pressed at 170℃ and 15MPa for 10min, and then treated at high temperature in a 200℃ oven for 30min.

[0045] Example 3

[0046] Weigh 142.5g of dendritic silver-coated copper powder, 17.5g of P-type flaky carbonyl iron powder, 42.5g of Q-type spherical carbonyl iron powder, and 57.5g of boron nitride nanosheets, mix them at a speed of 20rpm for 1.0h, then add 3.9g of coupling agent into the barrel, mix at room temperature for 1.0h, and obtain a wave absorbing and thermally conductive composite powder after activation treatment;

[0047] Weigh 40g of methylphenyl silicone rubber and composite powder, knead and mix at 11rpm for 13min in the first stage, 18rpm for 12min in the second stage, and 9rpm for 9min in the third stage, then add 1.0g of fumed silica and 0.40g of di-tert-butyl peroxide diisopropylbenzene, knead and mix at 23rpm for 10min in the first stage and 16rpm for 3min in the second stage; further, pass the rubber material 4 times with a roller distance of 1.1mm in the first stage and a roller distance of 1.1mm in the second stage. 0.7mm thin pass 6 times, three-stage roller spacing 0.3mm thin pass 3 times; then the sheet slurry and 0.1mm thick boron nitride fiber are calendered and compounded and stacked in 7 layers; then the sheet is placed between two 1700Gs magnetic field strength neodymium iron boron magnets with a spacing of 12cm and treated for 5 hours, further cut into 2cm wide strips of rubber, turn each strip over and then stick them together; finally, hot press at 155℃ and 12MPa for 12min, and then high temperature treatment in a 200℃ oven for 30min.

[0048] Comparative Example

[0049] Weigh 220g Q-type carbonyl iron powder and 40g methylphenyl silicone rubber and add them to the internal mixer, knead and stir for 1h to form a gray electromagnetic slurry; then weigh 0.5g fumed silica and 0.4g diisopropylbenzene ditert-butyl peroxide, add them to the electromagnetic slurry and stir for 10min to form an uncured flexible electromagnetic slurry; repeatedly thin the slurry on an open mill with a roller spacing of 0.4mm for 16 times, and then adjust the roller spacing to 2.0mm to roll out a sheet. Put the sheet rubber into a flat mold, hot press at 145℃ and 10MPa for 10min, and then high-temperature treat it in a 200℃ oven for 30min.

[0050] The test results of electromagnetic parameters, attenuation coefficient and thermal conductivity in Examples 1-3 and Comparative Examples are listed in Table 1

[0051] Table 1 Test results of electromagnetic properties, thermal conductivity and density of wave-absorbing and heat-conducting flexible electromagnetic functional composite materials

[0052]

[0053]

[0054] It can be seen from the data in Table 1 that by optimizing the proportion of various types of fillers and applying magnetic control arrangement measures, the material's high-frequency electromagnetic attenuation, thermal conductivity and lightweight are improved.

[0055] Although the present invention has been disclosed as above by way of embodiments, it is not intended to limit the present invention. Appropriate modifications or equivalent substitutions of the technical solutions of the present invention made by ordinary technicians in the field should all be included in the protection scope of the present invention. The protection scope of the present invention shall be based on what is defined in the claims.

Claims

1. A method for preparing a wave-absorbing, heat-conducting, flexible electromagnetic functional composite material, characterized in that the steps include: (1) premixing dendritic silver-coated copper powder, P-type carbonyl iron powder, Q-type carbonyl iron powder, and boron nitride nanosheets to obtain a thermally conductive and microwave-absorbing composite powder; (2) adding a coupling agent to the obtained thermal conductive and wave absorbing composite powder, mixing the mixture, and obtaining an activated thermal conductive and wave absorbing composite powder; (3) adding the activated heat-conducting and wave-absorbing composite powder to methylphenyl silicone rubber for initial mixing to obtain a wave-absorbing and heat-conducting electromagnetic slurry; (4) adding a certain amount of fumed silica and diisopropylbenzene di-tert-butyl peroxide to the obtained wave-absorbing and heat-conducting electromagnetic slurry, performing secondary mixing, and obtaining a flexible electromagnetic slurry after mixing evenly; (5) repeatedly thin-passing the obtained flexible electromagnetic slurry material, and then pressing it into a thin sheet of rubber material; (6) calendering the obtained flaky rubber material and the boron nitride fabric for preforming, and then stacking them into an unvulcanized prepreg; (7) placing the obtained unvulcanized prepreg between two magnets for arrangement, then cutting it into strips and laying them flat, then flipping the strips 90° horizontally and laminating them side by side to obtain a layered unvulcanized strip; (8) The obtained layered unvulcanized rubber material is subjected to hot pressing and vulcanization molding to obtain a wave-absorbing, heat-conducting, flexible and electromagnetic functional composite material.

2. The preparation method according to claim 1, characterized in that According to the mass percentage, 127.5-178.5 parts of dendritic silver-coated copper powder, 12.75-25.5 parts of P-type flaky carbonyl iron powder, 12.75-51 parts of Q-type spherical carbonyl iron powder, 51-63.75 parts of boron nitride nanosheets, 1.275-5.1 parts of coupling agent, 40-45 parts of methylphenyl silicone rubber, 0.5-1.2 parts of fumed silica, and 0.4-0.45 parts of di-tert-butyl peroxide diisopropylbenzene are weighed.

3. The preparation method according to claim 1, characterized in that: In step (1), the length of the dendritic silver-coated copper powder filler is 11-18 μm, the particle size of the P-type flaky carbonyl iron powder D50 is 3.5-6.0 μm, the particle size of the Q-type spherical carbonyl iron powder D50 is 3-5 μm, and the particle size of the boron nitride nanosheet D50 is 0.05-0.2 μm; the pre-mixing condition is mixing at a rotation speed of 12-25 rpm for 1-2 hours.

4. The preparation method according to claim 1, characterized in that: In step (2), the coupling agent is one of KH-550, KH-560, A-151, and GR-401; the mixture is mixed and treated at room temperature for 0.5-2h.

5. The preparation method according to claim 1, characterized in that: In step (3), the initial mixing is 30-40 minutes, and the specific mixing conditions are 10-12 rpm for 12-15 minutes in the first stage, 15-20 rpm for 10-15 minutes in the second stage, and 8-10 rpm for 8-10 minutes in the third stage; in step (4), the secondary mixing is 10-15 minutes, and the order of adding materials is as follows: adding fumed silica in the first stage and adding diisopropylbenzene tert-butyl peroxide in the second stage. The specific mixing conditions are 20-25 rpm for 8-11 minutes in the first stage and 15-18 rpm for 2-4 minutes in the second stage.

6. The preparation method according to claim 1, characterized in that: In step (5), the thin pass treatment is repeated 10-16 times. The thin pass treatment is divided into three stages: the first stage is a thin pass with a roller distance of 1-1.2 mm for 3-5 times, the second stage is a thin pass with a roller distance of 0.6-0.8 mm for 5-7 times, and the third stage is a thin pass with a roller distance of 0.2-0.4 mm for 2-4 times.

7. The preparation method according to claim 1, characterized in that: The calendering preforming condition in step (6) is to calender the composite at 5-8 rpm and then stack them to form a 7-layer thickness.

8. The preparation method according to claim 1, characterized in that: In step (7), two NdFeB magnets with a spacing of 8-15 cm are placed in the middle for magnetron treatment, the magnetic field strength is 1200-1850 Gs, and the magnetron treatment time is 4-6 hours; and then the rubber material is cut into 1-3 cm wide strips.

9. The preparation method according to claim 1, characterized in that: The hot pressing vulcanization molding conditions in step (8) are hot pressing at 145-170° C. and 10-15 MPa for 10-15 min, and post-treatment at 200° C. for 30 min.

10. A wave-absorbing, heat-conducting, flexible, electromagnetic functional composite material, characterized in that: Prepared by the preparation method according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Multi-layer coating

    CN115678422A

  • High-thermal-conductivity polyacrylate pressure-sensitive adhesive and preparation method thereof

    CN117186796A

  • Electromagnetic wave shielding sheet and electromagnetic wave shielding wiring circuit board

    JP6690773B1

  • Complex sheet having electromagnetic shielding and thermal dissipation abilities and absorbing electromagnetic waves at specfic frequency range, and methods of manufacturing the same

    KR1020180068561A

  • Thermally conductive thin film sheet and article comprising same

    US20190210322A1